Architectural achievements of the Fatimid state in central Maghreb. - rahli, saliha (Journal of Social Sciences and Humanities, 2024)
The history of the countries of the Maghreb has gone through Important historical events that made it the headquarters of the various sectarian and political, currents that found the appropriate place for those fleeing with their gifts and ideas from the Abbasid authority in Baghdad, and fir that the country became a fertile ground from the dissemination and crystallization of these ideas which allowed the emergence of independent states in different historical periods, whether it was a state belonging to the Abbasid state in east or separate from it, enjoying independence and the coming management of the affairs of government ,And among them are the mini-states of the Fatimid state, which made the Middle Maghreb, the first nucleus for spreading their shirt gift with the help of the Berber tribes, especially the Gautama tribe ,the state also worked to consolidate its pillars in the country and adopted several policies aimed at giving continuity to the Fatimid’s in controlling the country Maghreb .Among these policies was the establishment of a group of cities In different parts of the country in order to tighten their control more aver the region and to cub the rebellion of the Barbarian tribes against their authority, as the cities later became major capitals in the region and among the cities, we mention the fondation of the city of M sila in central Maghreb.